Active Heave Compensation Control of ROVS. Issue 2 (17th July 2012) - Li, Jia‐Wang; Ge, Tong; Wang, Xu‐Yang
Abstract To keep the remotely operated vehicles (ROVs) motion unaffected by the ship's motion in the vertical direction, a nonlinear active heave compensation controller is designed in this paper. The compensation system consists mainly of an electro‐hydraulic system driven by a double rod cylinder. Based on the external model principle, an adaptive observer is proposed to asymptotically estimate the ship's heave motion represented by a set of sinusoidal signals. The hybrid control development and stability analysis are based on the Lyapunov's direct method and backstepping technique. The proposed controller forces the tracking error to globally asymptotically converge to a small zone around zero that can be reduced arbitrarily. Simulation results illustrate and validate the effectiveness of the proposed control scheme.